Extraction of triple and evaluation of exact matching using keywords on Durian HTML document / Nur Fathihah Ismail - Ismail, Nur Fathihah (2014)
Search engine is used to retrieve information from the World Wide Web. However there is a deluge amount of documents retrieved by a given query from the user. Users have difficulty to select relevant documents. With semantic search engine, user can acquire relevant document that is sufficient enough that answer user query. Research has been shown that semantic search engine performs better than available search engine. However to build a semantic search engine requires representing deluge information in triples. In this project. Semantic Search Engine for Durian is built. Firstly, documents from html documents related to Durian and query are collected. Triples from selected documents are extracted and saved. Secondly, matching using query words procedures is built. Finally the matching procedure is evaluated using the search engine known as King. The result shows that the matched documents are the relevant to the queries collected.